Epidemiological Study of Scorpion-sting in Patients Referred to Medical Centers of Shiraz, South-west of Iran - Masoumeh Bagheri; Hamzeh Alipour; Ali Keshawarz (Shiraz University of Medical Sciences, 2021)
Background: Scorpion sting is one of the serious and major medical problems in the world. Shiraz is a tourist city and one of the high-risk areas where a number of scorpion sting occurs annually. Objectives: The present research aimed to conduct an epidemiological study of scorpion sting in Shiraz County. Methods: The is a cross-sectional study  performed using a checklists to collect data about scorpionism in Shiraz health center during 2014-2018. Results: The results of the study showed that the total number of scorpion stings was 844 cases. generally, 336  cases (39.8%) were female and 508 s (59.3%) male. The results from the residential area revealed that 817 cases (96.8%) were urban and 27 (3.1%) were rural. The highest frequency of scorpionism happened in the 25-34 years old group (286,33.8%) and after that 15-24 year old (165,19.4%), 35-44 year old (157, 18.6%), 45-54 year old (108, 12.7%) groups, and the least  frequency awas seen in the 0-4 year old group. The time periods between the sting and injection of anti-venom were less than 6 hours for 822, (85.5%) of cases, 6-12 hours for 101, (11.9%) of cases and, more than 12 hours for 21 (2.4%)  cases. A total of 844 cases were recovered; 690 (81.7%) of them recovered with anti-venom and 154 (18.2%) injured individuals recovered without any anti-venom, the sting site was 27.6% in the foot, 57% in the hand, and 20% in the head and trunk. Conclusion: Shiraz is a major tourist city, and most cases of scorpion-sting occur in summer and spring, when the tourist population is high, so health care providers must carry out an integrated program in those months.